Peningkatan Kepercayaan Diri melalui Bimbingan Klasikal Berbasis Group Discussion dan Media Bamboozle - Hafsya Afra Nadhifah; Muhammad Arif Budiman Sucipto; Rahmad Agung Nugraha (UPT Publikasi dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2025)
The analysis of the Student Needs Assessment Questionnaire (AKPD) indicated that 3.26% of respondents experienced problems related to low self-confidence. This study aims to examine students’ understanding of self-confidence before and after receiving classical guidance through the group discussion method assisted by Bamboozle Media, as well as to evaluate its effectiveness in enhancing self-confidence among seventh-grade students of class VII B at SMP Negeri 12 Kota Tegal. The research employed a quantitative approach with a pre-experimental one-group pre-test and post-test design, involving 32 students with low self-confidence who were selected using purposive sampling. Data were collected through questionnaires, observation, and documentation. The research instrument showed high reliability, with a Cronbach’s Alpha score of 0.945. Data analysis employed normality tests, homogeneity tests, and a paired sample t-test. Findings revealed that the mean self-confidence score increased from the pre-test average of 78.21 (moderate category) to the post-test average of 170.18 (high category). Statistical testing showed a significant difference with a t-value of -40.096 and a Sig. (2-tailed) value of 0.000 < 0.05, thus Ha was accepted. Effect size analysis using Cohen’s d yielded a score of 9.566, which indicates very large practical significance. This study provides strong empirical evidence that classical guidance through group discussion, supported by interactive digital media, is highly effective in improving students’ self-confidence, thereby offering innovative strategies for school counselors in the digital era. ____________________________________________________________Analisis Angket Kebutuhan Peserta Didik (AKPD) menunjukkan 3,26% responden menghadapi masalah kepercayaan diri rendah. Penelitian ini bertujuan mengetahui tingkat pemahaman kepercayaan diri peserta didik sebelum dan sesudah diberikan bimbingan klasikal melalui metode group discussion berbantuan media Bamboozle, serta menguji efektivitasnya dalam meningkatkan pemahaman kepercayaan diri siswa kelas VII B SMP Negeri 12 Kota Tegal. Penelitian menggunakan pendekatan kuantitatif dengan desain pre-experimental one group pre-test dan post-test, melibatkan 32 siswa dengan kepercayaan diri rendah yang dipilih melalui purposive sampling. Teknik pengumpulan data menggunakan angket, observasi, dan dokumentasi, dengan instrumen reliabel (Cronbach’s Alpha 0,945). Analisis data mencakup uji normalitas, homogenitas, dan paired sample t-test. Hasil menunjukkan rata-rata skor kepercayaan diri meningkat dari 78,21 (kategori sedang) pada pre-test menjadi 170,18 (kategori tinggi) pada post-test. Uji statistik menemukan perbedaan signifikan (t = -40,096; Sig. 0,000 < 0,05), sehingga Ha diterima. Analisis effect size menunjukkan Cohen’s d = 9,566 yang mengindikasikan signifikansi praktis sangat besar. Penelitian ini menegaskan bahwa bimbingan klasikal dengan metode group discussion berbantuan media digital interaktif Bamboozle terbukti sangat efektif meningkatkan pemahaman kepercayaan diri siswa, serta memberikan kontribusi nyata pada praktik bimbingan dan konseling di sekolah.